L07 The functional rating taskforce for pre-huntington's disease: development of the furst-21 scale. (29th August 2012) - Vaccarino, A; Anderson, K; Borowsky, B; Craufurd, D; Giuliano, J; Guttman, M; Ho, A; Landwehrmeyer, B; Paulsen, JS; Sills, T; Evans, K; ,
Abstract : Background: There is a need for clinical scales specifically designed to measure the earliest clinical manifestations of Huntington disease (HD) and to track early changes in clinical symptoms in HD gene expansion carriers. Such a measurement tool could be used to evaluate the effect of novel therapies early in the course of disease. Aims: The Functional Rating Scale Taskforce for pre-HD (FuRST-pHD) is a multinational, multidisciplinary collaboration to develop a valid functional rating scale to assess changes in symptom severity in prodromal (prHD) or early manifest HD gene expansion carriers. Methods: FuRST-pHD has established a process for scale development using input from numerous sources, including HD individuals and companions, experts from a variety of fields, as well as from data mining of ongoing observational studies in HD. FuRST-pHD utilised an iterative process in which changes to items are made based on empirical evidence obtained during field testing in prHD and early HD individuals, utilising various types of analyses, including Item Response and Rasch analyses, factor analysis, correlations and descriptive analyses, as well as clinical judgement. The criteria for item reduction and modification include assessment of item discrimination, relevance and response range, item redundancy, and convergent validity. Results: A total of 115 structured interview questions were developed to assess the presence and severity of motor, cognitive and psychiatric symptoms, as well as day-to-day functioning. Following multiple testing iterations in 784 prHD/early HD participants, a 40-item FuRST V1.0 was subsequently tested in prHD/early HD gene carriers (n=97), of which 21 items have been retained for inclusion in the primary scale (FuRST-21). Conclusions: FuRST-21 is a structured interview that shows promise as a tool to measure symptoms in prHD and early HD. Validation of FuRST-21 is currently in the planning stages.